Application of AES 256 Cryptography Algorithm OCB Mode on Student Data - Nora Febitri; Harry Witriyono; Muntahanah Muntahanah; Marhalim Marhalim (Jurnal Komputer, Informasi dan Teknologi, 2023)
In today's digital era, student data is very important and must be kept secure. Cryptography is a technique for securing data from unauthorized parties. AES 256 (Advanced Encryption Standard 256) is a cryptographic algorithm used to secure data with a symmetric key and uses OCB (Offset Codebook Mode) mode. The application of the OCB mode AES 256 cryptographic algorithm to student data will provide better protection against unauthorized access or data manipulation. This will be very important to maintain the confidentiality and integrity of confidential and private student data such as personal data, grades, and academic track records. In this study it can be concluded that the use of AES-256 in OCB mode is a good choice to protect student data with a high level of security. The combination of AES-256 and OCB provides a very high level of security for sending sensitive data over the network. OCB mode uses message encoding with offset, which allows use of shorter keys, making it more efficient than other modes of encryption operation.